2016
DOI: 10.3390/ijerph13080771
|View full text |Cite
|
Sign up to set email alerts
|

Severe and Moderate Asthma Exacerbations in Asthmatic Children and Exposure to Ambient Air Pollutants

Abstract: Background: It is well established that short-term exposure to ambient air pollutants can exacerbate asthma, the role of early life or long-term exposure is less clear. We assessed the association between severe asthma exacerbations with both birth and annual exposure to outdoor air pollutants with a population-based cohort of asthmatic children in the province of Quebec (Canada). Method: Exacerbations of asthma occurring between 1 April 1996 and 31 March 2011 were defined as one hospitalization or emergency r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…e adverse effects of PM on hospitalizations for cardiovascular disease were correlated with the same day of pollutant increase (lag 0) and decreased the risk on subsequent days [27][28][29][30]. e present study also differs from the academic literature that shows an association between PM 2.5 and the increase in hospitalization for cardiorespiratory diseases [31][32][33]. e literature shows that for children, an increase in the PM 2.5 level increased the number of hospitalizations for respiratory diseases [34][35][36][37].…”
Section: Resultscontrasting
confidence: 53%
“…e adverse effects of PM on hospitalizations for cardiovascular disease were correlated with the same day of pollutant increase (lag 0) and decreased the risk on subsequent days [27][28][29][30]. e present study also differs from the academic literature that shows an association between PM 2.5 and the increase in hospitalization for cardiorespiratory diseases [31][32][33]. e literature shows that for children, an increase in the PM 2.5 level increased the number of hospitalizations for respiratory diseases [34][35][36][37].…”
Section: Resultscontrasting
confidence: 53%
“…Ambient air pollution (PM 2.5 ) severely victimizes people having a history of respiratory disease like chronic obstructive pulmonary disease (COPD) [5,18]. The literature has validated the contributive impact of air pollution (PM 2.5 ) in onset of various respiratory diseases like respiratory infection, chronic obstructive pulmonary disease (COPD), asthma, and lung cancer [19,20,21,22,23]. [24] found strong association between air pollution and respiratory disease mortalities and outpatient visits in southeastern China.…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 is generated by automobiles and gas heaters and cooking ranges. Recent studies have shown a link between NO 2 exposure and reduced lung function (3*, 4*), increased need for rescue medications (28), and elevated risk and severity of asthma exacerbations (9, 11, 29). Gaffin et al reported that for every 10 ppb increase in classroom NO 2 concentration, there was a 5% reduction in FEV 1 /Forced Vital Capacity (FVC) ratio; classroom NO 2 was inversely associated with Forced Expiratory Flow at 25–75% of lung volume (FEF 25- 75) in this study (3*).…”
Section: Introductionmentioning
confidence: 99%